Pharmacist prescribing in Australia - Hoti, Kreshnik (Curtin University, 2010)
Expanded pharmacist prescribing is emerging as a new practice area for pharmacists. This study aimed at exploring pharmacists’ and pharmacy clients’ views on this issue. Improved medication supply models in residential aged care facilities (RACFs), including expanded pharmacist prescribing were also explored. Pharmacists and pharmacy clients supported an expanded prescribing role for pharmacists. A centralised medication chart model was preferred in RACFs with pharmacist prescribing having only a limited role.